Circular Dichroism of Chromaffin Granule Proteins In Situ: Analysis of Turbidity Effects and Protein Conformation - Rosenheck, Kurt (1973)
The circular dichroism spectra for proteins in situ in catecholamine secretory vesicles (chromaffin granules) is presented together with an analysis of protein conformation and turbidity effects on the spectra. The calculational analysis has resolved scattering and absorption effects in the turbid suspension spectra using a coated-sphere scattering model which allows for different materials in its shell and core. The intrinsic conformation of the proteins in situ was estimated by an iterative procedure with various trial protein conformations, for the chromaffin granules both intact and after release of their contents. The resulting average secondary structures (within about 10%) are: (25% α helix, 15% β structure) for the membrane proteins and (15% α helix, 5% β structure) for the soluble contents. The protein conformation did not change with osmotic release of the granule's contents. Consequently, if chromogranins are involved in a catecholamine storage complex, this is not reflected in any detectable change in their average secondary structure.